2018
DOI: 10.1016/j.jchf.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy in Inotrope-Dependent Heart Failure Patients

Abstract: This study suggests that rescue CRT may be considered a viable therapeutic option in inotrope-dependent patients with HF. In these patients, rescue CRT may allow them to be weaned from inotropic therapy, improve their quality of life, and decrease the rate of mortality; furthermore, rescue CRT may serve as a possible bridge to cardiac transplantation or left ventricular assist device therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Although several studies have tried to evaluate the efficacy of CRT in this patient population, the current study offers several merits over the previous ones 6–12,17–20 . First, our study population, which was composed only of FA‐IV HF patients, was more homogeneous than others 17–20 ; in a previous investigation, only one‐third of patients exhibited NYHA class‐IV symptoms 19 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although several studies have tried to evaluate the efficacy of CRT in this patient population, the current study offers several merits over the previous ones 6–12,17–20 . First, our study population, which was composed only of FA‐IV HF patients, was more homogeneous than others 17–20 ; in a previous investigation, only one‐third of patients exhibited NYHA class‐IV symptoms 19 .…”
Section: Discussionmentioning
confidence: 95%
“…Recently, several studies have shown that CRT did improve HF symptoms and survival rates of some IVD‐supported HF patients with FA‐IV status, although the overall outcomes were not as good as in HF patients with less disease severity; 1‐year survival ranged from 40% to 80% 6–12,17,26,27 . A beneficial effect of rescue CRT implantation for inotrope‐dependent HF patients was also demonstrated in a recently published meta‐analysis that incorporated 151 patients from eight related studies 20 . The success rate for weaning from IVDs was 93%, and the overall 1‐year survival rate was 69% after CRT in their pooled analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cardiac transplantation remains the gold standard for these patients but death on the waiting list has become an increasing problem due to shortage of donor organs. Although randomized data are lacking for this population, a recent meta-analysis suggests that rescue CRT in inotrope-dependent patients may allow the weaning of the majority of patients from intravenous inotropic support, reduce mortality and thus be used as a bridge-to-transplant or to a ventricular assist device in suitable patients [17]. Usually, a CRT-D system should be used in this situation as a similar benefit has been shown in the US in a large retrospective analysis of the Organ Procurement and Transplantation Network (OPTN)/United Network for Organ Sharing (UNOS) registry for the ICD [18].…”
Section: Advanced Versus Mild Heart Failurementioning
confidence: 99%